2023
DOI: 10.1111/bju.15994
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal graft ureteroplasty versus ileal ureteric replacement: a meta‐analysis

Abstract: ObjectivesTo describe outcomes of oral mucosal graft ureteroplasty (OMGU) and ileal ureter replacement (IUR) and determine the relative merits of both procedures. MethodsDatabases (including PubMed, Embase and Cochrane) were interrogated for eligible trials that assessed outcomes of OMGU or IUR from 2000 to 30 July 2022. The variables analysed were reconstruction success rates, stricture length, hospital stays, perioperative complications and long-term complications. ResultsA total of 23 single-arm studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…In contrast to this, none of our patients had complications at the BMG donor site, two had a postoperative UTI, and one patient had an incision hernia approximately one year after the procedure. A recent meta-analysis of OMG ureteroplasty versus ileal ureteric replacement by You et al supports these findings of lower complication rates and less severe complications for OMGs opposed to intestinal interposition [ 11 ]. The technique described in this study uses an onlay approach.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In contrast to this, none of our patients had complications at the BMG donor site, two had a postoperative UTI, and one patient had an incision hernia approximately one year after the procedure. A recent meta-analysis of OMG ureteroplasty versus ileal ureteric replacement by You et al supports these findings of lower complication rates and less severe complications for OMGs opposed to intestinal interposition [ 11 ]. The technique described in this study uses an onlay approach.…”
Section: Discussionmentioning
confidence: 85%
“…Intestinal interposition bears many risks including bowel anastomosis leakage, impaired bowel movement or ileus, mucus obstruction of the urinary tract, and recurrent urinary tract infections (UTI) [ 11 , 15 ]. Additionally, the long-term exposure of urine to ileal mucosa presents a risk for the development of metabolic acidosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of long proximal ureteral stricture (US) remains a challenge for urologists. Since the first case of laparoscopic lingual mucosal graft ureteroplasty (LMGU) was introduced by Li et al in 2015 ( 1 ), it received extensive attention as an efficient way to avoid ileal ureter replacement or renal autotransplantation for ureteral reconstruction ( 2 ). Recently, Yang et al reported the technique and initial experience of robotic LMGU with encouraging perioperative and medium-term follow-up outcome ( 3 ).…”
Section: Introductionmentioning
confidence: 99%